2019
DOI: 10.3390/molecules24203737
|View full text |Cite
|
Sign up to set email alerts
|

Natural Sesquiterpene Lactones of the 4,15-iso-Atriplicolide Type are Inhibitors of Trypanothione Reductase

Abstract: In the course of our investigations on the antitrypanosomal potential of sesquiterpene lactones (STL), we have recently reported on the exceptionally strong activity of 4,15-iso-Atriplicolide tiglate, which demonstrated an IC50 value of 15 nM against Trypanosoma brucei rhodesiense, the etiologic agent responsible for East African human trypanosomiasis (HAT). Since STLs are known to often interact with their biological targets (e.g., in anti-inflammatory and anti-tumor activity) by means of the covalent modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In order to further evaluate whether F1012-2 induces an increase in ROS levels, we pretreated with antioxidant N-acetyl-L-cysteine (NAC) for 2 hours and found that ROS was completely eliminated by NAC (Figure 3(b)). Recent studies have shown that sesquiterpene lactones can bind to nucleophilic thiol compounds, including L-cysteine [25], which may explain this phenomenon. 7 BioMed Research International to facilitate the repair of DNA or initiate the apoptosis mechanism when DNA damage cannot be repaired.…”
Section: F1012-2 Induces Ros Overproduction In Mda-mb-231mentioning
confidence: 99%
“…In order to further evaluate whether F1012-2 induces an increase in ROS levels, we pretreated with antioxidant N-acetyl-L-cysteine (NAC) for 2 hours and found that ROS was completely eliminated by NAC (Figure 3(b)). Recent studies have shown that sesquiterpene lactones can bind to nucleophilic thiol compounds, including L-cysteine [25], which may explain this phenomenon. 7 BioMed Research International to facilitate the repair of DNA or initiate the apoptosis mechanism when DNA damage cannot be repaired.…”
Section: F1012-2 Induces Ros Overproduction In Mda-mb-231mentioning
confidence: 99%
“…In an attempt to explain other possible mechanisms of action of cumanin and its derivatives and taking into consideration that STLs have shown interaction with TcTR, , a molecular docking study of compounds 1 – 9 was carried out. The criteria of including all cumanin series were based on the wide range of IC 50 values obtained on T.…”
Section: Resultsmentioning
confidence: 99%
“…Other STLs such as deoxymikanolide and STLs of the 4,15-iso-atriplicolide type have affected or have shown inhibition of TcTR. 23,24 The most promising STLs, compounds 2 and 7, showed ΔG dock in the range of komaroviquinona, a terpenoid compound that was taken as a reference for the study. It was found that the residues Glu466B, Ser470B, and Arg472B were involved in H-bonding of the most active STLs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, furanoheliangolide-type STLs, characterized by the presence of Michael-acceptor structural motifs, were demonstrated to be endowed with high-level in vitro activity against Trypanosoma brucei rhodesiense [55]. In their work, Lenz and colleagues [56] studied the molecular basis of the activity of different furanoheliangolides. The STL 4,15-iso-atriplicolide tiglate and its homologues were demonstrated to inhibit trypanothione reductase (TR), an enzyme playing a critical role in the metabolism and survival of trypanosomatids.…”
Section: Inhibition Of Trypanothione Reductase By 415-iso-atriplicolmentioning
confidence: 99%